P382 FOLLOW–UP OF PATIENTS SUBMITTED TO TRANSVENOUS LEAD EXTRACTION FOR ENDOCARDITIS OR SEPTIC SHOCK AND THEN RE–IMPLANTED WITH LEADLESS PACEMAKER: SINGLE CENTER'S EXPERIENCE. (18th May 2022) - Dentico, A; Ferrieri, A; Epicoco, G; Troccoli, R; Carretta, F; D'Agostino, C; Carretta, D
Abstract: Introduction: With increasing of complications associated with pacemakers and defibrillators implants, the number of patients that undergo transvenous lead extraction following an infection increased. Often in pacemaker–dependent patients there is the problem of having to make an early re–implanting after extraction. This study aims to evaluate the incidence of reinfection in patients implanted with leadless PM following extraction. Materials and Methods: From January 2016 to December 2021, 132 extractions have been performed in our center. Of these post–extracted patients, 21 were then implanted with a leadless. Among the remaining, in 25 were re–implanted with a traditional PM, 27 with a defibrillator, 2 with a loop recorder, 3 are protected with Life Vest waiting for re–implant; 54 are patients who, after cardiological revaluation, or have not re–implanted a new device or have been redirected to the first implant's center waiting to complete antibiotic therapy. To evaluate the technical efficiency of leadless in post–extracted patients, a comparison was made between these and the leadless PM implanted "de novo". To demonstrate the reduction of reinfection recurrences, the post–operative of patients re–implanted with leadless has been compared to those re–implanted with traditional PM. To test the patient's level of approval to the new implanted device, a questionnaire was administered to the two samples. Results: A first analysis of the follow–up of the above classes from 2016 to today shows that in patients who have implanted a leadless PM in no case a recurrence of infection has occurred; in patients who have implanted a traditional device, we have seen how some of these had already suffered a revision of pocket, an extraction or leads' abandonment. The statistics of electrical parameters have demonstrated the effectiveness of the leadless in both classes of patients compared. Finally, the rating index questionnaire has shown greater acceptance of the new implanted device and a better patient–device relationship in patients re–implanted with leadless. Conclusions: The implant of Leadless Pacemaker in post–extracted patients, when we have eligible patients to implant this device, has proved to be an effective choice in reducing reinfection recurrences.